Associations of cognitive reserve and psychological resilience with cognitive functioning in subjects with cerebral white matter hyperintensities. (25th May 2021) - Arola, Anne; Laakso, Hanna M.; Pitkänen, Johanna; Koikkalainen, Juha; Lötjönen, Jyrki; Korvenoja, Antti; Erkinjuntti, Timo; Melkas, Susanna; Jokinen, Hanna
Abstract: Background and purpose: Cerebral small vessel disease is characterized by progressive white matter hyperintensities (WMH) and cognitive decline. However, variability exists in how individuals maintain cognitive capabilities despite significant neuropathology. The relationships between individual cognitive reserve, psychological resilience and cognitive functioning were examined in subjects with varying degrees of WMH. Methods: In the Helsinki Small Vessel Disease Study, 152 subjects (aged 65–75 years) underwent a comprehensive neuropsychological assessment, evaluation of subjective cognitive complaints and brain magnetic resonance imaging with volumetric WMH evaluation. Cognitive reserve was determined by education (years) and the modified Cognitive Reserve Scale (mCRS). Psychological resilience was evaluated with the Resilience Scale 14. Results: The mCRS total score correlated significantly with years of education ( r  = 0.23, p  < 0.01), but it was not related to age, sex or WMH volume. Together, mCRS score and education were associated with performance in a wide range of cognitive domains including processing speed, executive functions, working memory, verbal memory, visuospatial perception and verbal reasoning. Independently of education, the mCRS score had incremental predictive value on delayed verbal recall and subjective cognitive complaints. Psychological resilience was not significantly related to age, education, sex, WMH severity or cognitive test scores, but it was associated with subjective cognitive complaints. Conclusions: Cognitive reserve has strong and consistent associations with cognitive functioning in subjects with WMH. Education is widely associated with objective cognitive functioning, whereas lifetime engagement in cognitively stimulating leisure activities (mCRS) has independent predictive value on memory performance and subjective cognitive complaints. Psychological resilience is strongly associated with subjective, but not objective, cognitive functioning. Abstract : The figure from the word document titled "graphical TOC" Cerebral small vessel disease is characterised by progressive white matter hyperintensities (WMH) and cognitive decline. Variability exists in how individuals maintain cognitive capabilities despite significant neuropathology. We found cognitive reserve to have consistent associations with both objective and subjective cognitive functioning in subjects with varying degrees of WMH. Education has strong associations with a wide range of cognitive domains. Engagement in cognitively stimulating activities across lifetime is independently associated with delayed verbal memory and subjective cognitive complaints. Finally, psychological resilience is important for subjective, but not objective cognitive functioning.